PELATIHAN PENGGUNAAN GOOGLE ADVERTISING SEBAGAI INSTRUMEN UNTUK MEMPROMOSIKAN PRODUK PT CROWN PRATAMA - Sudirgo, Tony; Brian, Gilbertus; Tjahjadi, Lydia Suryani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
A country's economy is a continuous cycle of production and consumption of goods and services,this cycle is the most important area that supports the life of a country, and has a dominant effect on stability in various fields, especially the social, political, cultural and security of a country. One of the real evidences is the 1998 riots which was motivated by the weakening of the Indonesian economy due to the Asian Financial Crisis at that time. Companies as one of the driving wheels of the economy in a country are one of the country's largest contributors in terms of income, and employment. So that optimization is needed in maintaining the cycle of income and expenses so that the existing expenses are not greater than the income earned. One of the many problems often experienced by companies is in the field of marketing goods / services. Examples of service problems here are often associated with a lack of confidence in the quality and experience and services possessed. while in goods are often, more associated with the price and quality of the product. However, in many cases it can be seen that many companies in Indonesia engaged in services have not been able to fully maximize digital marketing to encourage the company to achieve sales targets and obtain expected profits. This PKM is a step to educate the partner company, PT CROWN PRATAMA, in optimizing one of the popular digital marketing instruments, Google Advertising, which uses machine learning technology to learn consumer behavior and interest in goods/services and present the right advertisements. This PKM is carried out on-site at PT CROWN PRATAMA using the PPT presentation method accompanied by a question and answer process. Hopefully this activity can provide knowledge and be useful for companies in utilizing advertising advances in this digital era.